Language curriculum development from a complex nonlinear system perspective - Hassan Soleimani; Majid Ghelichi (penerbit ukm, 2014)
The present position paper aims to provide a renewed definition of curriculum development in general and English as a foreign language (EFL) curriculum development in particular. In so doing, it will not only re-conceptualize curriculum development as a multifaceted and dynamic process of interrelated components but also introduce a new direction for looking at curriculum renewal from the lens of complex system theory. To this end, the features of both curriculum development in the field of English language teaching and the features of complex nonlinear systems in physical sciences will be discussed in an attempt to apply the features of the latter to the development of a language curriculum. It has been argued that, as is the case with complex nonlinear systems, a language curriculum can also be considered a complex nonlinear system in which different components are at work and the interactions among them are unpredictable. Furthermore, it has been discussed that the success or failure of a language curriculum will depend not on each single component of the curriculum but is the product of the interrelationships and interactions among the various components. Therefore, the development of a language curriculum should not be considered a step-by-step linear process. Rather, it should be considered as the unpredictable product of the behavior of and interactions among a complex set of variables and factors functioning in a nonlinear complex way.